Effect of Sargassum sp. Cultivation on Laboratory Scale with Different Substrates - Fitriani, Fitriani; Cokrowati, Nunik; Mukhlis, Alis (Jurnal Media Akuakultur Indonesia, 2023)
Sargassum sp. is a brown algae containing alginate and iodine ingredients used in the food, pharmaceutical, cosmetic and textile industries. The purpose of this study was to analyze the effect of substrate type on the growth of Sargassum sp and to determine the type of substrate that is good in Sargassum sp. This research was conducted from December 2022 to January 2023, at the Fish Production and Reproduction Laboratory, Aquaculture Study Program, Faculty of Agriculture, University of Mataram. This research was conducted using experimental methods and using substrate difference treatment. The experimental design used in this study was a complete randomized design consisting of 5 treatments and 3 repeats. The treatment is treatment A (without substrate), B (white sand), C (white sand and coral), D (black sand), E (volcanic rock). The results showed that treatment C showed the highest growth yield with the measured growth parameters being absolute growth, relative growth, specific growth rate. This study concluded that the type of substrate did not have a significant effect (not significantly different) on the growth of Sargassum sp. which are cultivated on a laboratory scale. Nevertheless, Sargassum sp. Those cultivated using a mixture of white sand and coral (C) substrates tended to have higher growth values compared to no substrate (A), white sand (B), black sand (D), and volcanic rock (E) with an absolute growth value for 35 days of 22.0 g, relative growth of 73.3%, and a specific growth rate of 1.6%. Alginate content of Sargassum sp. In the white sand substrate treatment tends to be higher than the other four treatments with an alginate percentage of 56.5%.